Primary care sleep medicine : a practical guide - Pandi-Perumal, S. R.; Pagel, James F. (Springer New York, 2014)
Diagnosing and treating sleep disorders have been added to the primary care physician's list of ever-growing responsibilities. This added expectation presents many risks since sleep medicine is rarely included in the curricula of medical schools or in non-sleep medicine residency training.   The second edition to Primary Care Sleep Medicine fulfills the need of a comprehensive text assisting the physician with up-to-date information on the sleep medicine field. This updated volume represents the cutting edge of knowledge for the field, with summaries of the latest research on new diagnostic tests, medications and therapies; useful for any physician considering specialization in the field. Chapters are authored by leaders in the field of sleep medicine with an understanding of the primary care environment.    Practical and comprehensive, this text is an invaluable resource for physicians and allied health professionals.